Odpowiedzi

2011-08-11T09:27:06+02:00

Rozpatrzę dwa przypadki w zależności od tego co jest w mianowniku w pierwsszym nawiasie:

 

1)

 

\frac{\sqrt3+2}{\sqrt3-2}+\frac{1-16\sqrt6}{4}=\frac{\sqrt3+2}{\sqrt3-2}\cdot\frac{\sqrt3+2}{\sqrt3+2}+\frac{1-16\sqrt6}{4}=\\=\frac{(\sqrt3+2)\cdot(\sqrt3+2)}{(\sqrt3-2)(\sqrt3+2)}+\frac{1-16\sqrt6}{4}=\frac{(\sqrt3+2)^2}{3-4}+\frac{1-16\sqrt6}{4}=\frac{3+4\sqrt3+4}{-1}+\frac{1-16\sqrt6}{4}=\\=\frac{7+4\sqrt3}{-1}+\frac{1-16\sqrt6}{4}=-7+4\sqrt3+\frac{1}{4}-\frac{16\sqrt6}{4}=\\=-7+4\sqrt3+\frac{1}{4}-4\sqrt6=4\sqrt3-4\sqrt6-6\frac{3}{4}

 

2)

 

\frac{\sqrt3+2}{\sqrt3}-2+\frac{1-16\sqrt6}{4}=\frac{\sqrt3+2}{\sqrt3}\cdot\frac{\sqrt3}{\sqrt3}-2+\frac{1-16\sqrt6}{4}=\\=\frac{(\sqrt3+2)\cdot\sqrt3}{\sqrt3\cdot\sqrt3}-2+\frac{1}{4}-\frac{16\sqrt6}{4}=\frac{3+2\sqrt3}{3}-2+\frac{1}{4}-4\sqrt6=\\=\frac{3}{3}+\frac{2\sqrt3}{3}-2+\frac{1}{4}-4\sqrt6=1+\frac{2}{3}\sqrt3-2+\frac{1}{4}-4\sqrt6=\\=\frac{2}{3}\sqrt3-4\sqrt6-\frac{3}{4}